(untitled) (Italian Journal of Food Safety, 2026)
A challenge test was conducted to evaluate the efficacy of three Spianata Piccante formulations (A: traditional; B: with a bacteriocin-producing starter culture; C: with added dextrose) in reducing experimentally inoculated Listeria innocua, used as a surrogate for Listeria monocytogenes, and Salmonella spp. The aim was to identify the formulation that best ensured pathogen inactivation in compliance with United States (US) export requirements. Traditional Italian salami are considered shelf-stable due to multiple hurdle technologies, including pH reduction, decreased water activity and competitive microflora. However, these hurdles are often insufficient to reduce foodborne pathogens, particularly L. monocytogenes and Salmonella spp., to the levels required by the Food Safety and Inspection Service (FSIS) regulations (≥3 log₁₀ CFU/g for L. monocytogenes and ≥5 log₁₀ CFU/g for Salmonella spp.). High-pressure processing (HPP), a non-thermal treatment capable of inactivating vegetative pathogens, can be applied to achieve these reductions. In this study, meat batter was inoculated prior to stuffing (6 log₁₀ CFU/g), and pathogen reductions were evaluated after ripening and HPP treatment. Significant differences in microbial inactivation were observed among formulations (p<0.05). Under the worst-case scenario, defined as the lowest log₁₀ reduction among all tested units, only formulation B met the FSIS validation targets, achieving reductions of 3.89 log₁₀ CFU/g for L. innocua and 5.77 log₁₀ CFU/g for Salmonella spp. These findings suggest that the use of bacteriocin-producing starter cultures, combined with HPP, represents an effective strategy to enhance the microbiological safety of fermented dry-cured sausages intended for the US market.